2020
DOI: 10.48550/arxiv.2012.00917
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modelling a $2.5 \, M_{\odot}$ Compact Star with Quark Matter

J. E. Horvath,
P. H. R. S. Moraes

Abstract: The detection of an unexpected ∼ 2.5M component in the gravitational wave event GW190814 has puzzled the community of High-Energy astrophysicists, since in the absence of further information it is not clear whether this is the heaviest "neutron star" ever detected or either the lightest black hole known, of a kind absent in the local neighbourhood. We show in this work a few possibilities for a model of the former, in the framework of three different quark matter models with and without anisotropy in the inter… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In the standard interpretation [32][33][34][35][36][37][38] this is either the most massive neutron star observed to date or is a black hole that is located in the so-called mass-gap. Other, more exotic models include for example a strange star [39,40] or a compact star in an alternative theory of gravity [41]. The neutron star interpretation of the light companion in the GW190814 challenges our current understanding of the EoS, even if one assumes that this star is rotating very rapidly [32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…In the standard interpretation [32][33][34][35][36][37][38] this is either the most massive neutron star observed to date or is a black hole that is located in the so-called mass-gap. Other, more exotic models include for example a strange star [39,40] or a compact star in an alternative theory of gravity [41]. The neutron star interpretation of the light companion in the GW190814 challenges our current understanding of the EoS, even if one assumes that this star is rotating very rapidly [32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…A possibility of distinguishing quark stars in standard or CFL phase from low mass black holes or neutron stars could be through the study of thin accretion disks around rapidly rotating stars (neutron or quark), and Kerr type black holes, respectively. It was already suggested that the GW190814 event resulted from the merging of a black hole -strange quark star system [10][11][12]. Some compact astrophysical objects may contain a significant part of their matter in the form of a Bose-Einstein condensate.…”
Section: Introduction 1 II Action and Field Equationsmentioning
confidence: 99%